On the edge—A diagnostic odyssey. Issue 4 (7th April 2022) - McLean, Hailey; Palmquist, Rachel; Nadauld, Lincoln D.; Malone Jenkins, Sabrina; Bonkowsky, Joshua; Filloux, Francis
Abstract: The diagnostic odyssey of a child with epileptic encephalopathy was resolved by rapid whole genome sequencing. This identified a rare form of pyridoxine responsive epilepsy due to a pathogenic variant in PLPBP . Access to such potentially life‐changing diagnostic technology needs to expand in a thoughtful and equitable manner. Abstract : Technology continues to rapidly improve our ability to diagnose rare diseases. We must ensure that access to life‐changing technology expands in an intentional way. As science advances so must our focus on values of compassion, justice, and equity.